2017
DOI: 10.1007/s40722-017-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

High waves in Draupner seas—Part 1: numerical simulations and characterization of the seas

Abstract: Extreme waves are studied in numerical simulations of the so-called Draupner seas that resemble the wave situation near the observation area of the Draupner wave, an iconic example of a freak, rogue wave. Recent new meteorological insights describe these seas as a substantial wind-generated wave system accompanied by two low-frequency lobes. With the significant wave height H s = 12 m above a depth of 70 m and the wide directional spreading over 120 • as design information, results are presented of simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It has also been shown that for certain angles, crossing seas may also enhance the occurrence of modulational instability (Onorato, Osborne & Serio 2006;Toffoli et al 2011b;Cavaleri et al 2012). For the Draupner wave in a water depth d = 70 m and with a zero-crossing period T z = 12.5 s, the non-dimensional water depth kd = 1.6 (k is the wavenumber) is probably not sufficiently above the limit of 1.36 for modulational stability to have played an important role (Cavaleri et al 2016) Beyond its overall wave height of h = 25.6 m (height abnormality index h/H s = 2.13, where H s is the significant wave height, defined as four times the standard deviation of the surface elevation) and crest height of a = 18.5 m (crest abnormality index a/H s = 1.55), the Draupner wave is exceptional in a number of other ways (see Janssen 2015;Cavaleri et al 2016;van Groesen, Turnip & Kurnia 2017, for a discussion of its likelihood). First, the wave group itself was accompanied by what is most probably a set-up of the wave-averaged free surface, whereas a set-down is expected in the absence of crossing (Walker et al 2004).…”
mentioning
confidence: 99%
“…It has also been shown that for certain angles, crossing seas may also enhance the occurrence of modulational instability (Onorato, Osborne & Serio 2006;Toffoli et al 2011b;Cavaleri et al 2012). For the Draupner wave in a water depth d = 70 m and with a zero-crossing period T z = 12.5 s, the non-dimensional water depth kd = 1.6 (k is the wavenumber) is probably not sufficiently above the limit of 1.36 for modulational stability to have played an important role (Cavaleri et al 2016) Beyond its overall wave height of h = 25.6 m (height abnormality index h/H s = 2.13, where H s is the significant wave height, defined as four times the standard deviation of the surface elevation) and crest height of a = 18.5 m (crest abnormality index a/H s = 1.55), the Draupner wave is exceptional in a number of other ways (see Janssen 2015;Cavaleri et al 2016;van Groesen, Turnip & Kurnia 2017, for a discussion of its likelihood). First, the wave group itself was accompanied by what is most probably a set-up of the wave-averaged free surface, whereas a set-down is expected in the absence of crossing (Walker et al 2004).…”
mentioning
confidence: 99%
“…The a posteriori simulation of generated waves can, for instance, be used to take the Fig. 5 The 2D spectrum as shown in [8] based on [16] Fig. 6 Plot of the sea state at time 2048.7 s looking from south (bottom) to north over the whole observation area.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for outflow in the simulation domain, in Sect. 3.3 we use data-assimilated influx, for which repeatedly known field data in a subdomain (instead of from a line) are merged with waves from an ongoing simulation in the complementary remaining domain [8].…”
Section: Wave Generation and Boundary Damping Zonesmentioning
confidence: 99%
See 1 more Smart Citation